Experimental study on single slope single basin solar still using TiO2 nano layer for natural clean water invention. (August 2020) - Shanmugan, S.; Essa, F.A.; Gorjian, Shiva; Kabeel, A.E.; Sathyamurthy, Ravishankar; Muthu Manokar, A.
Highlights: Modified solar still with nanolayer coating in the basin liner is studied. Mixing TiO2 nanoparticles with the coating to be used in basin area liner. Efficiency of the system is 57.16% in summer and 36.69% in winter. Average daily yield of solar still is 5.39 L in winter and 7.89 L in summer. Abstract: In the present study, solar still performance has been investigated under different operating conditions such as coating the basin liner by TiO2 nanoparticles mixed with Cr2 O3 and different combinations of hybrid bond adsorption. The basin liner was a copper sheet which was used to adsorb energy in winter & summer (W&S). The mixture of TiO2 nanoparticles and Cr2 O3 was characterized by SEM, FTIR and XRD tests. Results revealed that the average daily productivity of the solar still was 5.39 and 7.89 L during the winter and summer, respectively. The average daily efficiency of the system was 57.16% and 36.69% through the summer and winter, respectively. Based on the analysis, the best performance of the solar still can be achieved during winter and summer conditions of K L University of Andhra Pradesh, India. Graphical abstract: Image, graphical abstract